Isolation and characterization of Saccharomyces species for bioethanol production from sugarcane molasses: Studies of scale up in bioreactor - Muruaga, María Laura (2016)
Decreases in oil reserves and gas fields around all over the world justify the deepening of studies to render viable the larger-scale use of new energy sources. Therefore, the use of microorganisms to convert sugars into ethanol is a feasible process to be performed in a short period of time and at low costs. In this context, this study aimed to select ethanol-producing yeasts, after isolating samples in molasses obtained from companies in the Province of Tucumán (Argentina) and grapes obtained from farms located in Cafayate (Salta, Argentina). Among the twenty-nine samples studied A2, A10 and A11 isolates showed higher ethanol productions of 12.87; 13.64 and 13.46% respectively. A2 showed a homogeneous growth meanwhile the growth of strains A10 and A11 was flocculent. Molecular taxonomic characterization of these isolates showed a percentage of similarity of 100% with the strain Saccharomyces cerevisiae. The behavior of the non-flocculent A2 strain at laboratory scale was faster using a sugarcane molasses based medium, reaching 11.36% ethanol without adding nutrients and other growth factors, probably because its disperse form facilitates the transfer of nutrients and products. These values were improved to 12.02% when the process was scaled up to a 10L bioreactor. All these studies allowed concluding that S. cerevisiae A2 strain is a promising microorganism for the production of bioethanol with potential environmental, energy and economic benefits to be projected into industrial scale.